2014
DOI: 10.1016/j.mar.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Performance effects of multiple control forms in a Lean organization: A quantitative case study in a systems fit approach

Abstract: The primary objective of this paper is to research and test how control forms function and perform in a Lean organization. In the present quantitative case study, we provide statistical support that Lean is a set of multiple control forms (output, behavioral, and social controls) that complement each other to enhance performance, i.e., it is a control package. Therefore, performance is increased if the average level of control forms is increased, and performance is further increased if the control forms are ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 44 publications
(106 reference statements)
0
51
0
2
Order By: Relevance
“…Taken together, these contributions partially counter Kennedy and Widener's (2008), Fullerton, Kennedy, and Widener's (2013) and Kristensen and Israelsen's (2014) emphasis on accounting control and provide a more sophisticated and a more operations-centred view of how PM is structured and used in LMOs. In other words, our findings suggest that PM practices that have the most prominent relevance in an LMO may be those that are located closest to the actions on the shop floor and that explicitly address operational realities.…”
Section: Enabling Mechanisms Of Pm Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…Taken together, these contributions partially counter Kennedy and Widener's (2008), Fullerton, Kennedy, and Widener's (2013) and Kristensen and Israelsen's (2014) emphasis on accounting control and provide a more sophisticated and a more operations-centred view of how PM is structured and used in LMOs. In other words, our findings suggest that PM practices that have the most prominent relevance in an LMO may be those that are located closest to the actions on the shop floor and that explicitly address operational realities.…”
Section: Enabling Mechanisms Of Pm Systemsmentioning
confidence: 97%
“…In the MCS literature, Kristensen and Israelsen (2014) approximate this effect statistically, but stop short of identifying the actual mechanisms underlying the effect of control systems on performance. In the OM literature, Pavlov and Bourne (2011) make a step towards explaining this, but do so only conceptually.…”
Section: Introductionmentioning
confidence: 99%
“…For example, benchmarking could be used to share information about best practices and stimulate cooperation in improvement trajectories. Hence, where Kristensen and Israelsen (2014) showed that a balanced use of lean controls has a complementary effect on performance, the outcomes of this study suggest that there should also be a balance between these lean controls and the accounting-based controls that are important to HQ.…”
Section: Lean Implementation Strategiesmentioning
confidence: 66%
“…• Group B -has 6 articles divided into two small groups of common themes, formed by Articles (DEMETER; MATYUSZ, 2011;KRISTENSEN;ISRAELSEN, 2014;PAIVA, 2010;WIENGARTEN;PAGELL, 2012;BORTOLOTTI;BOSCARI;DANESE, 2015;GONZALEZ;MARTINS, 2014). …”
Section: Independent Journal Of Management and Production (Ijmandp)mentioning
confidence: 99%